Some Comments on Devaluation of Schorlary Degrees: An Economic-sociological Analysis of Dynamics of Academic Status Symbols - Михаил Михайлович Соколов (Journal of Economic Sociology, 2010)
This study has two objectives. First, it suggests conceptual tools, which allows without breaking methodological consistency to sum up divergent commonsense views explaining why devaluation of symbols of academic status takes place and how to resist it. Second, it investigates possibilities for convergence of three separate perspectives in economics and sociology: a) refelxive pragmatics of social symbolism by Goffman and Garﬁ nkel [Goffman 1951; Goffman, 1959; Goffman 1969; Garﬁ nkel 1967]; b) research on “social dilemmas” [Axelrod 1984; Ostrom 1990; Ostrom 1997]; c) information economics, especially see Spence [Spence 1976; Spence 1973; Spence 2002; Akerlof 1970; Stiglitz 2000; Riley 2001].